Clinical next‐generation sequencing in patients with non–small cell lung cancer. Issue 4 (24th October 2014) - Hagemann, Ian S.; Devarakonda, Siddhartha; Lockwood, Christina M.; Spencer, David H.; Guebert, Kalin; Bredemeyer, Andrew J.; Al‐Kateb, Hussam; Nguyen, TuDung T.; Duncavage, Eric J.; Cottrell, Catherine E.; Kulkarni, Shashikant; Nagarajan, Rakesh; et al.
Abstract : BACKGROUND: A clinical assay was implemented to perform next‐generation sequencing (NGS) of genes commonly mutated in multiple cancer types. This report describes the feasibility and diagnostic yield of this assay in 381 consecutive patients with non–small cell lung cancer (NSCLC). METHODS: Clinical targeted sequencing of 23 genes was performed with DNA from formalin‐fixed, paraffin‐embedded (FFPE) tumor tissue. The assay used Agilent SureSelect hybrid capture followed by Illumina HiSeq 2000, MiSeq, or HiSeq 2500 sequencing in a College of American Pathologists–accredited, Clinical Laboratory Improvement Amendments–certified laboratory. Single‐nucleotide variants and insertion/deletion events were reported. This assay was performed before methods were developed to detect rearrangements by NGS. RESULTS: Two hundred nine of all requisitioned samples (55%) were successfully sequenced. The most common reason for not performing the sequencing was an insufficient quantity of tissue available in the blocks (29%). Excisional, endoscopic, and core biopsy specimens were sufficient for testing in 95%, 66%, and 40% of the cases, respectively. The median turnaround time (TAT) in the pathology laboratory was 21 days, and there was a trend of an improved TAT with more rapid sequencing platforms. Sequencing yielded a mean coverage of 1318×. Potentially actionable mutations (ie, predictive or prognostic) were identified in 46% of 209 samples and were most commonly found in KRAS (28%), epidermal growth factor receptor (14%), phosphatidylinositol‐4, 5‐bisphosphate 3‐kinase catalytic subunit alpha (4%), phosphatase and tensin homolog (1%), and BRAF (1%). Five percent of the samples had multiple actionable mutations. A targeted therapy was instituted on the basis of NGS in 11% of the sequenced patients or in 6% of all patients. CONCLUSIONS: NGS‐based diagnostics are feasible in NSCLC and provide clinically relevant information from readily available FFPE tissue. The sample type is associated with the probability of successful testing. Cancer 2015;121:631–639. © 2014 American Cancer Society . Abstract : In a series of 381 consecutive non–small cell lung cancers submitted for clinical targeted next‐generation sequencing, sequencing was successfully completed in 209 (55%) and resulted in the adoption of a targeted therapy in 22 (11%).